Temporomandibular disorder as risk factor for radiation‐induced trismus in patients with head and neck cancer - Nina Pauli; Bodil Fagerberg Mohlin; Christina Mejersjö; Caterina Finizia (Wiley, 2022)
Abstract Objectives The aim of this study was to investigate if patients with temporomandibular disorders (TMD) prior to head and neck cancer (HNC) treatment are at higher risk of developing trismus after oncological treatment. Materials and Methods Eighty‐three study patients underwent detailed dental examination prior oncological treatment and 6 months after radiotherapy completion, including evaluation of temporomandibular jaw function, palpation of the jaw muscles, and measurement of mouth opening capacity. TMD criteria were based on both clinical examination findings and patient‐reported symptoms. TMD at baseline was used in regression analysis in order to predict restricted mouth opening. Results At the 6 months follow‐up more than a third of the patients (35%) were examined with reduced mouth opening of >20% compared to baseline. A majority of the patients had bilateral tenderness of both the temporal and the masseter muscle. At the 6 months follow‐up, 42% of the study patients reported mouth opening problems. About one‐third of the patients suffered from fatigue and stiffness of the jaw as well as pain when mowing the jaw. Two questions from the validated symptom‐specific Gothenburg Trismus Questionnaire were found to be related to a statistically significant increased risk of restricted mouth opening after radiotherapy; "During the last week, have you felt: Pain on moving the jaw?" (OR [95% CI] 5.9 (1.2-29.4) [p = 0.030]) and "During the last week, have you felt pain and tenderness in the muscles of mastication?" (OR [95% CI] 5.90 [1.19-29.40] [p = 0.030]). Conclusions TMD is common amongst HNC patients. Patients who suffer from pain in the jaw muscles and pain when moving the jaw before start of treatment are at higher risk of radiation‐induced trismus after 6 months. Clinicians should strive for optimizing the patients pain treatment and oral health before, during, and after radiotherapy.